2022
DOI: 10.29333/ejgm/11563
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Attitudes Towards Antibiotics Use and an Examination on Patient’s Unrealistic Health Symptoms in Turkey

Abstract: Background: This study aimed to assess the attitudes and knowledge of adult individuals about antibiotics. Since in Turkey, antibiotics are not sold without a prescription, it was also investigated whether Turkish people compelled physicians to prescribe antibiotics by showing unrealistic symptoms. Methods:A self-administered cross-sectional survey involving 1,057 respondents was conducted using a validated questionnaire. The questionnaire was prepared in four sections. The first section included attitude asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Moreover, Turkish inhabitants nowadays show appropriate attitudes and practices towards antibiotics and only a small portion declared that they put pressure on healthcare professionals to prescribe antibiotics [ 33 ]. Not all recent Turkish studies are predominantly positive about Turkish people’s attitudes and knowledge [ 35 , 36 ] and show that 16.9% of patients still force the physician to prescribe antibiotics [ 37 ], which may underline strong individual differences. Another explanation for the similarities between immigrant and native Dutch participants might be that cultural differences in healthcare mainly play a role when there are psychological issues or traumatic experiences that involve complex treatments [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Turkish inhabitants nowadays show appropriate attitudes and practices towards antibiotics and only a small portion declared that they put pressure on healthcare professionals to prescribe antibiotics [ 33 ]. Not all recent Turkish studies are predominantly positive about Turkish people’s attitudes and knowledge [ 35 , 36 ] and show that 16.9% of patients still force the physician to prescribe antibiotics [ 37 ], which may underline strong individual differences. Another explanation for the similarities between immigrant and native Dutch participants might be that cultural differences in healthcare mainly play a role when there are psychological issues or traumatic experiences that involve complex treatments [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Turkey, several studies have investigated the attitudes, knowledge and behaviours towards antibiotics [ 11 , 12 , 13 , 14 ], but only one surveyed more than one city [ 13 ]. A study of 945 Turkish university students and their friends and families found that over half (55.8%) reported having used antibiotics in the past 12 months, and over a third (34.2%) had self-medicated without a prescription [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study of 1057 Bursa residents found that many believed antibiotics could be used to treat bacterial infections (58.3%), viral infections (75.5%), as well as coughs, colds and the flu (60.4%) [ 11 ]. In addition, 64.5% believed it was correct to stop taking antibiotics when symptoms improved and that it was healthier to take fewer antibiotics than were prescribed (40.0%).…”
Section: Introductionmentioning
confidence: 99%